Agroforestry Small Landholder's Tool for Climate Change Resiliency and Mitigation - Shukla, Gopal; Chakravarty, Sumit; Panwar, Pankaj; Bhat, Jahangeer A. (IntechOpen, 2021)
The book is a collection of chapters that deal with agroforestry systems on small farms. It compiles a variety of suitable agroforestry systems that can both sequester carbon and mitigate climate change while also providing socio-economic benefits. The book also discusses the ways in which small landholders can use agroforestry to combat land degradation.